GEOLOGICAL AND GEOCHEMICAL COMPARISON OF SOUTHERN URALS AND SOUTH INDIAN CRYPTOCRYSTALLINE MAGNESITE - Prasannakumar V.; Krupenin M.T.; Gulyaeva T.Y.; Petrischeva V.G. (My University, 2004)
South Indian and Southern Urals cryptocrystalline magnesites, deposited in similar geological milieu, are broadly comparable in mineralogy and geochemistry. Magnesite mineralisation in South India is mostly associated with the rocks of ultramafic intrusive complex, forming a part of the metamorphosed volcano-sedimentary sequence. The ultramafic intrusive complex is composed of dunite, peridotite, pyroxenite, gabbro and their metamorphic products. In the Urals, magnesite deposits are located in the ultramafic massif of an ophiolitic belt. The cryptocrystalline magnesite has developed as stockwork of veins in the upper part of weathered ultramafic rocks in different parts of the massif. Both the deposits in South Indian and Southern Urals contain analogous mineralogy with magnesite + quartz + calcite + dolomite, but the Indian deposits contain admixture of talc + siderite also. In all the investigated samples the dominant mineral is magnesite (73 - 96%). Calcite (1 - 3%), dolomite (0 - 7%), siderite (0 - 2%), quartz (0 - 5%), talc (0 - 14%), and serpetine (0 - 2%) are the accessories. Chemical composition of magnesite from both areas indicates good quality, and some samples show slightly high contents of CaO (up to 2.6%) and FcO (up to 1.6%), resulting from secondary dolomite and siderite, respectively. The high contents of SiO2 up to 5 - 8% are due to the accessory quartz and talc. It is suggested that magnesite, in both the regions, was formed as precipitation in open fractures by ascending /descending hypogene/exogene waters, the presence of talc indicating low temperature of formation. The present study points to the need of exploring a global magnesite-forming event in the ultramafic complexes associated with ophiolite belts.